U.S. Private Saving and the Tax Treatment of IRA/401(k)s : A Re-examination Using Household Survey Data - Thomas, Alun (IMF Working Papers; Working Paper ;, 1996)
The effect of the tax treatment of IRA/401(k)s on U.S. personal saving is examined using household survey data from the Survey of Consumer Finances. The results suggest that the tax treatment of IRA/401(k)s encouraged households to increase the share of assets held in the form of pension savings, at the expense of saving in the form of housing equity. Some evidence also was found to suggest that the tax treatment of pension savings similarly affected the flow of saving. In particular, the data appeared to reject the hypothesis that the tax treatment of IRA/401(k)s increased total personal saving.